PENGARUH KONSENTRASI LARUTAN KOH PADA KARBON AKTIF TEMPURUNG KELAPA UNTUK ADSORPSI LOGAM Cu - Erlina Erlina; Umiatin Umiatin; Esmar Budi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The research on the manufacture of activated carbon made from coconut shell charcoal by using chemical and physical activation has been done. Chemical activation was done by soaking the granulated charcoal into the activator solution of Potassium Hydroxide (KOH). And physical activation was done by passing argon gas into the furnace. The purpose of this research was to determine the effect of variations concentration of the activator solution to the adsorption power of activated carbon for removed heavy metal Cu. Chemical activation was done by soaking the samples for 24 hours in a solution of KOH 30%, 40%, 50% and 60%. While the physical activation was done by using a horizontal furnace at a temperature of 400oC for 1 hour with argon gas flow rate of 200 kg/m3. Samples that have been activated were tested for their ability to adsorb Cu in solution Copper Sulfate. Filtration process used is a batch method, in which the samples were stored in waste and stirred using a magnetic stirrer. The results of analysis by Atomic Absorption Spectrophotometer (AAS) showed the highest adsorption efficiency by 50% KOH activation of 83.57%. And the results of tests that have been performed, the greater the concentration of KOH were given the higher efficiency of adsorption of the Cu metal. But for 60% KOH concentration adsorption efficiency decreases due to pore activated carbon saturated so that the adsorption power decreases.Key words: activated carbon, Potassium Hydroxide, Adsorption, heavy metal.